Gestational age and hospital admission costs from birth to childhood: a population-based record linkage study in England - Hua, X; Petrou, S; Coathup, V; Carson, C; Kurinczuk, JK; Quigley, MA; Rivero-Arias, O (BMJ Publishing Group, 2023)
Objective: To examine the association between gestational age at birth and hospital admission costs from birth to 8 years of age. Design: Population-based, record linkage, cohort study in England. Setting: National Health Service (NHS) hospitals in England, UK. Participants: 1 018 136 live, singleton births in NHS hospitals in England between 1 January 2005 and 31 December 2006. Main outcome measures: Hospital admission costs from birth to age 8 years, estimated by gestational age at birth (<28, 28–29, 30–31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41 and 42 weeks). Results: Both birth admission and subsequent admission hospital costs decreased with increasing gestational age at birth. Differences in hospital admission costs between gestational age groups diminished with increasing age, particularly after the first 2 years following birth. Children born extremely preterm (<28 weeks) and very preterm (28–31 weeks) still had higher average hospital admission costs (£699 (95% CI £419 to £919) for <28 weeks; £434 (95% CI £305 to £563) for 28–31 weeks) during the eighth year of life compared with children born at 40 weeks (£109, 95% CI £104 to £114). Children born extremely preterm had the highest 8-year cumulative hospital admission costs per child (£80 559 (95% CI £79 238 to £82 019)), a large proportion of which was incurred during the first year after birth (£71 997 (95% CI £70 866 to £73 097)). Conclusions: The association between gestational age at birth and hospital admission costs persists into mid-childhood. The study results provide a useful costing resource for future economic evaluations focusing on preventive and treatment strategies for babies born preterm.